Case report: Shock after percutaneous vertebroplasty of the 5th thoracic vertebra - Hao, Shenshen; Yu, Xin; Li, Laihao; Liu, Shuai; Li, Hongke; Dong, Shengli; Cao, Xinhao (Frontiers in Surgery, 2023)
Background: Percutaneous vertebroplasty (PVP) is a common treatment for osteoporotic vertebral compression fracture (OVCF). Perioperative bleeding is usually rare, so there are few reports of shock. However, we developed shock after treating a case of OVCF of the 5th thoracic vertebra with PVP. Case presentation: An 80 years old female patient received PVP due to OVCF of the 5th thoracic vertebra. The operation was successfully completed and the patient returned to the ward safely after the operation. At 90 minutes after operation, she developed shock, which was induced by subcutaneous hemorrhage up to 1500 mL at the puncture site. Before using vascular embolization, transfusion and blood transfusion were used to maintain blood pressure, and local ice bag compression was used to reduce swelling and stop bleeding, which achieved successful hemostasis. She recovered and discharged after 15 days, with the hematoma having absorbed. There was no recurrence during the 17-month follow-up. Conclusion: Although PVP is considered to be a safe and effective method to treat OVCF, the possible hemorrhagic shock still needs to arouse the vigilance of surgeons.